PENINGKATAN KESADARAN MASYARAKAT TERHADAP COVID 19, ISOMAN DAN VAKSINASI UNTUK MENGURANGI PENYEBARAN COVID-19 DI KAMPUNG TANJUNGSARI KOTA TASIKMALAYA - Keni Idacahyati; Ira Rahmiyani; Resti Anggraeni Safitri; Hamzah Afriansyah; Irna Fitriani; Winda Siti Wulandari; Via Hervina; Sifa Syamrotul Fuadah; Mochamad Doni Permana (LP2M Universitas Hasanuddin, 2023)
Coronaviruses are a large family of viruses that cause disease in humans and animals. In humans, it can cause respiratory tract infections, ranging from the common cold to serious conditions such as Middle East Respiratory Syndrome (MERS) and Severe Acute Respiratory Syndrome (SARS). In general, the transmission of this virus occurs through droplets or body fluids splashed on someone or objects around them, which is 1-2 meters away through coughing and sneezing. Public knowledge is very influential in behavior in prevention. This outreach activity to the community aims to provide education about the prevention of COVID-19 and public awareness to carry out vaccines. This community service is carried out in the form of distributing healthy community products in the form of turmeric and ginger herbs, medical masks, cloth masks, hand sanitizers, handsoap as well as providing education to the public regarding